MEASUREMENT OF LONGSOR LAND VULNERABILITY AS A DIFFICULTY PLAN FOR RESOURCES IN RESOURCES - Muhammad Nursa'ban; Sugiharyanto Sugiharyanto; Nurul Khotimah (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The objectives of this research are to: Investigating the level of landslide susceptibility and identifying the distribution of landslide susceptibility locations in Menoreh Mountains area. This is the explorative research. The subject of this research are Menoreh Mountains area in Bagelen, and Bener districts Purworejo regency, in addition to Samigaluh District in Kulonprogo Regency. Land units were chosen as the sample using the purposive area sampling technique. Thirty land units were obtained by overlay maps of slope, geology, and soil types. Data collecting was conducted with observation method and documentation to be analyzed by qualitative deskriptif. Findings shown that (I) the level of landslide susceptibility that is in four categories in Samigaluh and Bener districts are low, medium, high, and very high. While three categories were low, medium, and high clasified in Bagelen district. The distributions of low landslide susceptibility covered about 46.500.527,08 m2 (2 land units in Samigaluh, 3 land units in Bener, and 3 land units in Bagelen). The medium categories covered about 104480073,8 m2 (l land units in Samigaluh, 4 land units in Bener, and 7 land units in Bagelen). High categories covered about 67734399,31 m2 (each of district is 2 land units). The very high categories covered about 12228602,01 m2 (2 land units for both, Samigaluh and Bener District). Key words: landslide, susceptibility, mitigation, hazard, Menoreh